LMD-19. Anatomic and Surgical Factors Predict Development of Leptomeningeal Disease in Patients with Metastatic Melanoma. (9th August 2021) - Lowe, Stephen; Wang, Christopher P; Brisco, Amanda; Ahmed, Kamran; Vogelbaum, Michael A; Liu, James K C
Abstract: Background: Leptomeningeal disease (LMD) is a devastating complication of systemic malignancy, portending a poor prognosis with an estimated median survival of 4–6 weeks if left untreated. Several reports have suggested surgical resection, particularly piecemeal resection, as a potential causative factor. Herein, we explore if surgical and anatomical factors are correlated with development of LMD in patients with melanoma brain metastases. Methods: Patients treated at our institution between 1999–2019 for primary melanoma with brain metastasis were compiled into a database based on ICD9/10 coding. 1, 079 patients with melanoma brain metastases and appropriate imaging were identified, and 834 patients with a minimum of 3 months' follow up were included. Patients were dichotomized by development of LMD or lack thereof. General demographic information, surgical and anatomic data, and ventricular access during surgery were investigated as possible correlative factors for the development of LMD. Results: On univariate analysis, female gender (p=0.033), presence of dural metastasis (p=0.018), presence of periventricular lesions (p<.001), presence of intraventricular lesions (p<.001), and ventricular access during surgery (p<.001) were significantly associated with LMD. Patients undergoing surgery, or those undergoing surgery without ventricular access, were not at higher risk of LMD. Administration of immunotherapy, either as first-line or salvage therapy, did not impact rates of LMD. On multivariate analysis, female gender (p=.033), presence of periventricular lesions (p<.001), presence of intraventricular lesions (p<.002), and presence of dural metastasis (p=0.032) were significantly associated with development of LMD. In patients who had surgery, iatrogenic ventricular access (p<.001) was significantly correlated with LMD. Conclusions: In a retrospective cohort of patients with melanoma metastatic to the brain, those patients with pre-existing lesions in contact with the CSF space are more likely to develop LMD than those who do not. In addition, iatrogenic access to the CSF space during surgery is highly correlated with LMD development.